Perennial Candidates dalam Politik Lokal di Sulawesi Barat Indonesia - Oktav Pahlevi; Budi Setiyono; Fitriyah Fitriyah; Supratiwi Supratiwi; Muhammad Yusri AR (Bulletin of Indonesian Islamic Studies, 2024)
This paper investigates the phenomenon of perennial candidates—individuals who consistently run for local political office but fail to achieve victory. The focus of this study is Salim S. Mengga within the framework of local politics in West Sulawesi, Indonesia. Employing qualitative research methods, this work adopts an in-depth case study approach. Data collection involves interviews, field observations, and documentation, while data analysis utilizes complex time series techniques. The results indicate that the motivations driving perennial candidates, particularly the Mengga clan, are rooted in political clan egoism, a concept deeply embedded in Sulawesi society. The clan's repeated electoral defeats can be examined through institutional theory, which emphasizes their inability to maintain social capital. From the perspective of power theory, political contests are viewed as battles between clans, where victories are predominantly dependent on familial networks, often overshadowing the role of political parties. System theory suggests that the decline in the clan's cultural and symbolic capital adversely impacts their political power. Additionally, political economic theory attributes their failures to a lack of sufficient economic capital within the clan.